Investigation of university students’ perceptions of their eductors as role models and designers of digitalized curricula - Starčič, Andreja Istenič; Lebeničnik, Maja (Human Technology, 2020)
Higher education graduates need 21st-century skills, both learning skills and competences for working with technology. However, research indicates an insufficient integration of ICTs into teaching and learning. In this paper, we examine students’ perception of various technology-based issues: (a) ICT integration within a Slovenian university’s learning environment, (b) teachers as role models for ICT use, and (c) the processes of collaboration and creativity as integrative parts featured in learning technologies. We studied beliefs about the contribution of ICT use to teaching and learning as the primary factors influencing ICT integration. A one-way ANOVA revealed that students in teacher education and education studies, as compared to students in other disciplines, perceive their teachers as effective designers of and as role models for ICT integration, although they do not perceive their teachers as leaders in new technology use. Effective leadership in technology innovation and the diversity of instructional design in guided and student-driven learning environments require continual curriculum development.